2009
DOI: 10.1590/s0100-736x2009001100001
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of bovine coronavirus by a semi-nested RT-PCR

Abstract: RESUMO.-[Detecção rápida do Coronavírus Bovino (BCoV) por meio de uma semi-nested RT-PCR.]O Coronavírus bovino (BCoV) pertence ao grupo 2 do gêne-ro Coronavirus (Nidovirales: Coronaviridae) e é agente causador de enterites tanto em bezerros como em bovinos adultos, bem como de doença respiratória em bezerros. O presente estudo teve por objetivo desenvolver uma seminested RT-PCR para a detecção do BCoV com base em seqüências representativas e recentes do gene do nucleocapsídeo, região conservada do genoma dos c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 19 publications
0
15
0
2
Order By: Relevance
“…In order to detect BCoV, a reaction was carried out with semi‐nested RT‐PCR using specific primers for the gene that codes for BCoV N protein, as described by Asano et al . (). The RT‐PCR reaction was carried out by adding 2.5 μ L of RNA to the PCR mix (25 μ L of 2x Reaction Mix (Invitrogen™), 0.2 mmol/L of BCoV1 (5′AGAGCTCAAYCCAAGCAA ACTGY 3′) and BCoV2 (5′AG CAGACCTTCCTGAGCCTTCAAT 3′), 2 μ L of SuperScript III RT Mix ̸Platinum Taq (Invitrogen™) and 16 μ L of DEPC‐treated water to achieve a final volume of 25 μ L, heated to 94°C/4 min followed by 35 cycles of 94°C/1 min, 50.2°C/30 s, 72°C/45 s and 72°C/5 min for the final extension.…”
Section: Methodsmentioning
confidence: 97%
“…In order to detect BCoV, a reaction was carried out with semi‐nested RT‐PCR using specific primers for the gene that codes for BCoV N protein, as described by Asano et al . (). The RT‐PCR reaction was carried out by adding 2.5 μ L of RNA to the PCR mix (25 μ L of 2x Reaction Mix (Invitrogen™), 0.2 mmol/L of BCoV1 (5′AGAGCTCAAYCCAAGCAA ACTGY 3′) and BCoV2 (5′AG CAGACCTTCCTGAGCCTTCAAT 3′), 2 μ L of SuperScript III RT Mix ̸Platinum Taq (Invitrogen™) and 16 μ L of DEPC‐treated water to achieve a final volume of 25 μ L, heated to 94°C/4 min followed by 35 cycles of 94°C/1 min, 50.2°C/30 s, 72°C/45 s and 72°C/5 min for the final extension.…”
Section: Methodsmentioning
confidence: 97%
“…Though the semi-nested protocol has shown a high analytical sensitivity, with a detection limit at 10 -6 dilution of the Kakegawa strain, this sensitivity was lower when compared to those described by Asano et al 20 and Takiuchi et al 21 , who found a detection limit at the 10 -7 dilution of the Kakegawa strain of the same HA titer. Such dissimilarity may be due to the genomic region chosen as the target of the coding region of HE protein, which presents a higher diversity if compared to the coding region of N protein, a highly conserved region 22 , targeted by the authors of the aforementioned studies.…”
Section: Discussionmentioning
confidence: 64%
“…O BCoV é também autor de infecções respiratórias em bovinos de todas as idades, sendo identificado em amostras de animais convalescentes devido pneumonia, a partir de amostras de fezes, secreções nasais e em pulmões. Sua transmissão assemelha-se com as demais síndromes sendo predominante a forma respiratória (aerossóis) (Asano et al, 2009;Saif, 2010).…”
Section: Síndrome Respiratóriaunclassified